2017
DOI: 10.1002/eqe.2983
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of inelastic displacement ratio for base‐isolated structures

Abstract: Summary This study develops a straightforward approximate method to estimate inelastic displacement ratio, C1 for base‐isolated structures subjected to near‐fault and far‐fault ground motions. Taking into account the inelastic behavior of isolator and superstructure, a 2 degrees of freedom model is employed. A total of 90 earthquake ground motions are selected and classified into different clusters according to the frequency content features of records represented by the peak ground acceleration to peak ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In earthquake engineering, significant efforts have been made to investigate the destructive effects of the pulse-like © 2019 Computer-Aided Civil and Infrastructure Engineering ground motion on various civil structures, including idealized single (multi) degree-of-freedom systems (e.g., Guo, Yang, & Liu, 2018;Mollaioli, Bruno, Decanini, & Panza, 2006), seismically base-isolated structures (e.g., Mazza, 2018;Yaghmaei-Sabegh, Safari, & Ghayouri, 2017), bridge structures (e.g., Antonellis & Panagiotou, 2014), and some other special structures or structural elements (e.g., Nigdeli & Boduroğlu, 2013;Tian, Yi, & Qu, 2018;Yi et al, 2018). A state-of-the-art summary of key conclusions regarding the effects of near-fault ground motions on the structures can be found in the literature (e.g., Champion & Liel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In earthquake engineering, significant efforts have been made to investigate the destructive effects of the pulse-like © 2019 Computer-Aided Civil and Infrastructure Engineering ground motion on various civil structures, including idealized single (multi) degree-of-freedom systems (e.g., Guo, Yang, & Liu, 2018;Mollaioli, Bruno, Decanini, & Panza, 2006), seismically base-isolated structures (e.g., Mazza, 2018;Yaghmaei-Sabegh, Safari, & Ghayouri, 2017), bridge structures (e.g., Antonellis & Panagiotou, 2014), and some other special structures or structural elements (e.g., Nigdeli & Boduroğlu, 2013;Tian, Yi, & Qu, 2018;Yi et al, 2018). A state-of-the-art summary of key conclusions regarding the effects of near-fault ground motions on the structures can be found in the literature (e.g., Champion & Liel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These records should be compatible with the seismic hazard at the site and reflect the range of potential earthquake scenarios [61][62][63]. Moreover, statistical methods can be used to estimate the likely maximum displacement of the main structure [64][65][66].…”
Section: Influence Of Seismic Excitation Intensity On the Selection O...mentioning
confidence: 99%
“…24,25 Despite the potential significance of different seismic demands resulting from the two types of velocity pulses, investigations on this topic are limited, except for a few pioneer studies. To the best of our knowledge, authough there are plenty of studies contributing to the subject of C R , [29][30][31][32][33][34][35] no efforts have been devoted to analyzing the differences in terms of C R that are introduced by velocity pulses having different characteristics. In this regard, a new algorithm 26 for automatically classifying acc-pulses and non-acc-pulses can be implemented to perform a comparative study to reveal how the velocity pulses of different characteristics may affect the inelastic response of structures.…”
Section: Introductionmentioning
confidence: 99%
“…The "bumps" were also noted by previous studies, 29,30 but the reason of how these "bumps" are produced was not revealed. To the best of our knowledge, authough there are plenty of studies contributing to the subject of C R , [29][30][31][32][33][34][35] no efforts have been devoted to analyzing the differences in terms of C R that are introduced by velocity pulses having different characteristics. The pronounced differences in C R that are observed in this study highlight the importance of distinguishing acc-pulses and non-acc-pulses when selecting near-fault ground motions for carrying out nonlinear dynamic analysis.…”
Section: Introductionmentioning
confidence: 99%